KERENDAHAN HATI KARYA TAUFIK ISMAIL DAN BE THE BEST OF WHATEVER YOU ARE KARYA DOUGLAS MALLOCH: KAJIAN INTERTEKSTUALITAS - Syam, Essy (Jurnal Ilmu Budaya, 2017)
This writing analyzes the relationship between one text and another, in this case poems entitle Kerendahan Hati written by Taufik Ismail and another poem entitles Be the Best of Whatever You are written by Douglas Malloch. Thus, the objective of this analysis is to show and analyze the relationship between these two texts. To reach the objective, this analysis applies intertextuality to present the relations because intertextuality believes no text is original. It is true due to the signification of a text is influenced by the signification of other text, which are the reference or quotation of the previous text.Related to that idea, this analysis will describe how Kerendahan hati is related to Be the Best of Whatever You are. Furthermore, it will be concluded which text is the source. It will prove whether Kerendahan Hati is the source which influences Be the Best of Whatever You are or vice versa.